Phytochemicals and Antioxidative Properties of Borneo Indigenous Liposu (Baccaurea lanceolata) and Tampoi (Baccaurea macrocarpa) Fruits - Mohd Fadzelly Abu Bakar; Nor Ezani Ahmad; Fifilyana Abdul Karim; Syazlina Saib (MDPI AG, 2014)
Two underutilized indigenous fruits of Borneo, Liposu (Baccaurea lanceolata) and Tampoi (Baccaurea macrocarpa) were investigated for their total phenolic (TPC), flavonoid (TFC), anthocyanin (TAC) and carotenoid (TCC) contents as well as antioxidant properties in vitro. The fruits were separated into three different parts (i.e., pericarp, flesh and seed) and extracted using 80% methanol. Antioxidant activity was determined using DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging, ABTS decolorization and FRAP (Ferric Reducing Antioxidant Power) assays. The results showed that B. macrocarpa pericarp contained the highest amount of total phenolics, total flavonoid, total anthocyanin and total carotenoid with the values of 60.04 ± 0.53 mg GAE/g, 44.68 ± 0.67 mg CE/g, 1.23 ± 0.20 mg c-3-gE/100 g and 0.81 ± 0.14 mg BCE/g. Results from DPPH, ABTS and FRAP assays also showed that the pericarp of B. macrocarpa displayed the highest antioxidant capacity. The antioxidant activity of the extract was significantly correlated with the total phenolic and flavonoid contents, but not with the carotenoid contents. In conclusion, B. macrocarpa displayed high potential as natural source of phytochemicals with antioxidant properties.